Factors Influencing Consumer Attitudes Toward Online Purchasing Decisions in Tha Mai District, Chanthaburi Province - maneethai, Surayut; Phonglar, Suriya; Phalalert, Decha (Journal for Strategy and Enterprise Competitiveness, 2024)
This research aims to: 1) examine the demographic factors influencing consumer attitudes toward online purchasing decisions in Tha Mai District, Chanthaburi Province, and 2) investigate the marketing mix factors (7P’s) affecting consumer attitudes toward online purchasing decisions in the same area. Data were collected from a sample of 405 respondents using a convenience sampling method, as the target population has specific geographic characteristics. Descriptive statistics, including frequency, mean, and standard deviation, were used to analyze the data. Inferential statistics were employed through Pearson's Chi-Square test and multiple regression analysis. The research findings revealed the following: 1) Consumer attitudes toward online purchasing significantly depended on personal status regarding gender, with a statistical significance level of 0.01, particularly in the aspect of online shopping aligning with modern lifestyles. 2) Age significantly influenced the perception that online shopping provides quality products meeting consumer needs, with a statistical significance level of 0.01 3) Education level significantly affected the perception of online shopping’s alignment with contemporary lifestyles, with a statistical significance level of 0.01. 4) Income level significantly influenced the convenience of online shopping, especially its 24-hour availability, with a statistical significance level of 0.01. 5) Occupation significantly impacted the simplicity of online purchasing processes, with a statistical significance level of 0.05. Additionally, marketing mix factors significantly influenced attitudes toward online purchasing decisions. Specifically: 1) Price, place (distribution channels), promotion, process, and physical evidence had a statistically significant impact at the 0.01 level. 2) Product had a statistically significant impact at the 0.05 level.